Becoming, belonging, and between: Unexpected outcomes and curricular implications for study abroad. (April 2020) - Clarke, Anthony; Fan, Xinyan; Webb, Andrea; Zou, Weicheng
Abstract: Increasingly pre-service teacher education programs throughout the world are including study abroad experiences as part of their curriculum. In an attempt to understand the longer-term impact of these experiences, this study explores the significant memories of four successive cohorts of Chinese students (approximately 32 students/cohort) who undertook an intensive study abroad program in Canada between 2014 and 2017. In 2018, the students completed an online questionnaire about their experience. Using the constant comparative method to analyse the data, three unexpected themes emerged: Becoming, Belonging, and Between. These themes lead to a discussion of curricular implications (e.g., expedient versus educative) for study abroad. Highlights: Evaluations of study abroad are usually incidental; this research explores the more enduring, temporal impact. The data analysis presents three outcomes that are rarely found in the study abroad literature. This paper argues for a curriculum that is coherent and connected (not modular and separated). This paper discusses the tension between 'curriculum as expedient' and 'curriculum as educative'.